Penguatan Literasi Digital Melalui Pengenalan Artificial Intelligence (AI) di Kalangan Siswa SMAN 1 Batang Cenaku - Yeyendra .; Hengki Satria; Ummi Kalsum; R Tio Duta Pratama; Lia Agustin (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The rapid development of digital technology, particularly Artificial Intelligence (AI), highlights the need to strengthen digital literacy among secondary school students so that they can use technology critically and responsibly. This study aims to analyze the effect of strengthening digital literacy through the introduction of Artificial Intelligence (AI) on the digital literacy of students at SMAN 1 Batang Cenaku. This research employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The research sample consisted of 32 eleventh-grade students selected through purposive sampling. The research instrument was a validated digital literacy questionnaire. Data were analyzed using descriptive statistics, paired sample t-test, and N-Gain analysis. The results showed an improvement in students’ digital literacy after participating in the AI introduction program, with the average pretest score of 61.34 and the posttest score of 83.56. The paired sample t-test indicated a significant difference between pretest and posttest scores (p < 0.05), while the N-Gain value of 0.57 was categorized as moderate. These findings indicate that the introduction of Artificial Intelligence (AI) is effective in strengthening students’ digital literacy, particularly in terms of technological understanding, critical thinking, and awareness of digital ethics and security. Therefore, integrating AI-related content into learning activities is recommended to enhance digital literacy in secondary education.